2015
DOI: 10.1111/sms.12371
|View full text |Cite
|
Sign up to set email alerts
|

Plantar flexor neuromuscular adjustments following match‐play football in hot and cool conditions

Abstract: We assessed neuromuscular fatigue and recovery of the plantar flexors after playing football with or without severe heat stress. Neuromuscular characteristics of the plantar flexors were assessed in 17 male players at baseline and ∼30 min, 24, and 48 h after two 90-min football matches in temperate (∼20°C and 55% rH) and hot (∼43°C and 20% rH) environments. Measurements included maximal voluntary strength, muscle activation, twitch contractile properties, and rate of torque development and soleus EMG (i.e., ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Following 90 min of match-play reductions in VA of <2% (Girard et al 2015;Nybo et al 2013) and ~8% (Rampinini et al 2011) have been previously reported which is less than observed in this study (~16%, Fig. 2c).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Following 90 min of match-play reductions in VA of <2% (Girard et al 2015;Nybo et al 2013) and ~8% (Rampinini et al 2011) have been previously reported which is less than observed in this study (~16%, Fig. 2c).…”
Section: Discussioncontrasting
confidence: 73%
“…Soccer match-play also results in significant central fatigue; a reduced VA of the knee-extensors (~ 8%) following 90 min of football matchplay was first reported by Rampinini et al (2011). Smaller reductions of ~ 1.5% in VA of the plantar flexors have also been reported following 90 min matches in hot (43 °C) and temperate (~ 20 to 21 °C) environments (Girard et al 2015;Nybo et al 2013). However, in these investigations, the post-match fatigue assessments were recorded 30-40 min following the match, a time in which the degree of fatigue would have dissipated.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The uncoupling between VA and RMS responses might be a result of the characteristic of the measures, since VA is the sum of the responses of all the knee extensor muscles to the superimposed motor nerve stimulation, while the EMG is a muscle-specific index (Girard et al, 2015b). Furthermore, it is possible that the load sharing strategies of quadriceps femoris could be altered under fatigue and contribute to maintenance of the RMS value of the vastus lateralis muscle after the simulated game (Bouillard et al, 2014).…”
Section: Discussionmentioning
confidence: 99%